2019
DOI: 10.12820/rbafs.24e0104
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of physical activity and sedentary behavior in adolescents by accelerometer: a cross-sectional study

Abstract: The objective of this study was to analyze the level of physical activity and sedentary behavior (SB) in students from Minas Gerais, Brazil. It is a cross-sectional study with 153 participants of both sexes and had to be between 10 and 12 old. We carried out measurements of socioeconomic and anthropometric variables. Also, physical activity and sedentary behavior were measured using an accelerometer (MiniMitter, Actiheart®). The accelerometer was fixed on the chest and the participants should remain wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In addition, in Brazil, the rate of attendance of children and adolescents at school, from 7 to 14 years old, is approximately 96% 21 , which facilitates the access of researchers to students. The majority of Brazilian studies (approximately 86%) have used subjective measures to evaluate SB through self-reported questionnaires or interviews, which may compromise the quality of the measure, as these methods present less accuracy and poor correlation with device-derived measures 22 . Chastin et al 15 compared several subjective instruments of SB measurement with a device-derived measurement instrument and found that the first present great bias, low precision, and low correlation with the second, besides not presenting standardization between the domains and time reference that they aim to measure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in Brazil, the rate of attendance of children and adolescents at school, from 7 to 14 years old, is approximately 96% 21 , which facilitates the access of researchers to students. The majority of Brazilian studies (approximately 86%) have used subjective measures to evaluate SB through self-reported questionnaires or interviews, which may compromise the quality of the measure, as these methods present less accuracy and poor correlation with device-derived measures 22 . Chastin et al 15 compared several subjective instruments of SB measurement with a device-derived measurement instrument and found that the first present great bias, low precision, and low correlation with the second, besides not presenting standardization between the domains and time reference that they aim to measure.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to technological advances (smartphones, social networks, electric vehicles, etc. ), urban violence, and other barriers, there is a reduction in its levels among children, young people, and adults, and a consequent reduction in cardiorespiratory fitness levels (Butcher et al, 2008;Tenório et al, 2010;Lima-Junior et al, 2019;Silva et al, 2020). It should be noted that the data regarding the level of habitual physical activity among the military personnel of the AFs are not very precise, with some studies showing that their levels may be between 60 and 90% of active/very active individuals, depending on the instrument used (Martignago et al, 2016;Rocha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%